Isotope constraints on nitrogen dynamics in the upper water column of the South China Sea - Xiuli Yan; Jin-Yu Terence Yang; Min Nina Xu; Ehui Tan; Zhenzhen Zheng; Wenbin Zou; Minhan Dai; Shuh-Ji Kao (Frontiers in Marine Science, 2022)
The supply of nitrogen (N) from various external and internal sources into the euphotic zone, e.g., atmospheric N deposition (AND), upwelling, lateral intrusion, and remineralization, modulates the biogeochemical and climatic roles of oligotrophic oceans and complicates N dynamics in the upper water column (≤200 m). However, our ability to resolve the mechanisms controlling upper-ocean N cycling is limited by the lack of high-resolution vertical observations. Here, we analyzed concentrations and dual isotopes of nitrate (NO 3 – ) in the upper 200 m of the oligotrophic South China Sea. By examining dual isotopic signatures of NO 3 – (δ 15 N NO3 and δ 18 O NO3 ) and multiple associated parameters vertically throughout the upper water column, we resolved the dominant N sources and processes, including AND/N 2 -fixation, assimilative fractionation, and nitrification, and quantitatively evaluated their contributions in the vertical distribution of NO 3 – , which can be separated into the Δδ 18 O NO3 -positive (δ 18 O NO3−obs −δ 18 O NO3−200m >0) and Δδ 18 O NO3 -negative layers (δ 18 O NO3−obs −δ 18 O NO3−200m <0) according to the deviation in δ 18 O NO3 at a given depth (δ 18 O NO3-obs ) from that at 200 m (δ 18 O NO3-200m ). In the Δδ 18 O NO3 -positive layer, the NO 3 – assimilated by phytoplankton was largely sourced from nitrification (39 ± 11%) and AND/N 2 fixation (17-28%), whereas these two processes accounted for 17 ± 10% and 7 ± 6% of the total NO 3 – pool in the Δδ 18 O NO3 -negative layer. Considering a substantial contribution of the regenerated (nitrification-sourced) NO 3 – to the total NO 3 – pool especially in the Δδ 18 O NO3 -positive layer, caution should be taken that the new production assessed by the rates of NO 3 – uptake may be significantly overestimated in the SCS. These findings not only highlight the importance of these biogeochemical processes to NO 3 – dynamics in the upper water column of marginal seas, but also with important implications for the estimation of biological carbon pump and/or the f -ratio.